DEVELOPMENT OF ALUMINIUM METAL MATRIX COMPOSITE FOR PRODUCTION OF CENTRIFUGAL PUMP IMPELLER - Akindapo Jacob Olaitan; Garba Shehu; Daniel Ufuoma Orueri (Academy Journal of Science and Engineering)
This study aimed to develop an Aluminum Metal Matrix Composite (AMMC) reinforced with Silicon Carbide particulate (SiC) and Iron oxide (Fe2O3) for centrifugal pump impellers and related components. Using a laboratory-scale stir casting process, we created a composite material denoted as Al-8%SiC+6%Fe2O3+Mg+0.5%Cu+0.5%Ni. Aluminum formed the continuous phase, while SiC and Fe2O3 served as the primary reinforcements. SiC content remained constant at 8%wt, while Fe2O3 content varied at 0%, 2%, 4%, and 6%wt. The fabricated plate-type samples adhered to ASTM standards for consistent dimensions. The results revealed outstanding mechanical properties in optimal samples: Yield Strength (YS) of 122MPa, Ultimate Tensile Strength (UTS) of 138MPa, Flexural Strength (FS) of 171MPa, Hardness of 55.4HRA, and Density of 0.2482g/cm3. Microstructural analysis showed a homogeneous dispersion of reinforcements with occasional clusters. The composite with the best properties was chosen for a centrifugal pump impeller, which underwent testing on a Vj300 milling machine and delivered satisfactory performance. This study not only developed and characterized a novel AMMC but also demonstrated its successful use in a functional centrifugal pump impeller. These findings have significant implications for advancing materials science and engineering solutions across various industries.